Sex Offenders: Treat or Punish? (Community Quick Survey on Sex Offenders) - Rossy Sintya Marthasari (ANIMA Indonesian Psychological Journal, 2016)
The aim of this study was to collect data of what ordinary people think on chemical castration and the proper punishment for sex offenders. An online survey was conducted through a questionnaire (N = 36; 19 males and 17 females). Average age was between 19 and 61; all participants have heard and known about sexual harassment. Results showed that 21% of respondents concluded that the Internet was the main cause, 36% accused the pornographic films, 18% said that the harassment was due to how the victims behave and dress themselves, and 21% said that psychopathological factors also played a role. Most of the respondents advised that the proper punishment should be death penalty (47%), while 29% chose the chemical castration and 20% chose imprisonment. Since psychoterapy (in this context cognitive-behavioral therapy) combined with pharmacological therapy has shown better outcome compared to monotherapy, the author considers to involve cognitive behavioral therapy as part of rehabilitation, so psychotherapy should be part of punishment in lieu of chemical castration. Causes underlying the sexual harassments especially the psy-chological aspects are discussed.